2017
DOI: 10.1093/bja/aex245
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastometry guided fresh frozen plasma infusion for postpartum haemorrhage: OBS2, an observational study

Abstract: ISRCTN46295339 ( http://www.isrctn.com/ISRCTN46295339 ) (accessed July 24, 2017), EudraCT 2012-005511-11 ( https://www.clinicaltrialsregister.eu/ctr-search?query=2011-005511-11 ) (accessed July 24, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 30 publications
2
73
0
Order By: Relevance
“…Of the 203 women with EBL ≥ 1500 ml plus FibTEM A5 ≤ 12 mm, 187 had an ExTEM A5 < 47 mm. However, only 11 (5%) had an ExTEM CT > 100 s. These 11 women all exhibited severe clotting derangement, with ExTEM CT median (IQR [range]) 249 (136–293 [121–512]) s, FibTEM A5 3 (2–3 ) mm and ExTEM A5 10 (9–18 ) mm. Of these women, eight had placental abruptions of whom seven were associated with intra‐uterine death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 203 women with EBL ≥ 1500 ml plus FibTEM A5 ≤ 12 mm, 187 had an ExTEM A5 < 47 mm. However, only 11 (5%) had an ExTEM CT > 100 s. These 11 women all exhibited severe clotting derangement, with ExTEM CT median (IQR [range]) 249 (136–293 [121–512]) s, FibTEM A5 3 (2–3 ) mm and ExTEM A5 10 (9–18 ) mm. Of these women, eight had placental abruptions of whom seven were associated with intra‐uterine death.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, observational data from the study by Collins et al. found that withholding FFP in those without evidence of coagulopathy on point‐of‐care testing did not result in clinically significant haemostatic impairment .…”
Section: Discussionmentioning
confidence: 99%
“…At one of the institutions participating in the Collins et al. study , there were significant reductions in red blood cell and plasma usage, obstetric haemorrhages with blood loss > 2500 ml, and critical care admissions across the whole population during the time of the study. When this study ended in November 2015, there was an increase in large haemorrhages similar to before the study and a local inquiry identified themes such as: the multidisciplinary team not attending the mother's bed‐side quickly; a return to estimating blood loss instead of the more accurate gravimetric assessment; viscoelastic haemostatic assays not being performed early; and delays in obstetric and haemostatic interventions .…”
Section: When Should Viscoelastic Haemostatic Assays Be Used During Omentioning
confidence: 97%
“…This was demonstrated in the observational arm of a study by Collins et al. which enrolled 605 women experiencing moderate to severe postpartum haemorrhage . Fresh frozen plasma was not administered if FIBTEM A5 > 15 mm or bleeding had stopped.…”
Section: Viscoelastic Haemostatic Assays For Obstetric Haemorrhagementioning
confidence: 99%
See 1 more Smart Citation